PERAN PENGOBATAN ALTERNATIF Miftahussifa TERAHADAP KESEHATAN MASYARAKAT (Studi Pengobatan Alternatif di Desa Suka Makmur Kec. Gunung Sahilan) - Sari, Cahya Puspita; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Alternative medicine is now the main purpose besides hospitals for the community, especially rural or middle class people, with lower cost and easier distance in access one of Miftahussifa alternative treatment which now become one of the goals for Suka Makmur villagers for treatment. The purpose of this study is to find out how the system in doing Miftahussifa in the treatment and how the benefits for the health of the community around where Motivation is a theory that is used in which each patient must have the motivation to heal and find ways to do the healing as well as the five patients which was involved in this study. From the seam of patients in the find out where the alternative treatment Miftahussifa is very useful existence for the sick around the community with a cheaper cost and easy distance in access, but this treatment can also be done for people who do not have disease for do preventive treatment before illness.Keyword : Alternative Medicine